The Effect of REBT with the Rational Emotive Imagery (REI) Technique to Reduce Self-Injury in Class X Students of SMK Negeri 6 Medan - Citra Dewi Utami; Alfin Siregar (FKIP - Universitas Riau, 2026)
The focus of this study is to determine the effect of the Rational Emotive Behavior Therapy (REBT) approach using the Rational Emotive Imagery (REI) technique in reducing self-injury behavior among 10th grade students at SMK Negeri 6 Medan. The background of this study is based on the high tendency of adolescents to engage in self-injury as a maladaptive coping mechanism for emotional stress. The research method used was quantitative with a pre-experimental one-group pretest posttest design, involving four students selected through purposive sampling from 65 students. The data collection instrument, a self-injury scale, was analyzed using the Wilcoxon Signed-Rank test. The result demonstrated a significant reduction in self-injury levels following individual counseling interventions based on the REBT approach and REI technique, with a value of 0.046 (p < 0.05). These findings indicate that the REBT approach with REI techniques is effective in reducing students' self-injury behavior by changing irrational thinking patterns into rational ones, thereby enabling them to manage their emotions more adaptively. This study recommends the application of REI as a counseling strategy in schools to prevent and decrease self-harming behaviors in adolescents, such as self- injury.